1986
DOI: 10.1067/mva.1986.avs0030411
|View full text |Cite
|
Sign up to set email alerts
|

P nuclear magnetic resonance spectroscopy: Noninvasive biochemical analysis of the ischemic extremity

Abstract: The biochemical effects of peripheral vascular disease on skeletal muscle have not been characterized precisely because of the lack of satisfactory noninvasive analytic methods. 31P nuclear magnetic resonance (NMR) spectroscopy was used to measure the high-energy phosphate compounds, phosphocreatine (PCr) and adenosine triphosphate, as well as metabolic byproducts, such as inorganic phosphates (Pi) and phosphate monoesters in calf muscles of 214 limbs with peripheral vascular disease. Intracellular pH was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…While some studies reported hopeful outcomes of revascularization, linking to better bioenergetic status and muscle performance, other studies reported poor correlation of the improvement in hemodynamics measured by the ankle pressure index (API) and 31 P NMR index. While immediate improvements in hemodynamic responses and exercise tolerance may be seen after revascularization, the NMR index may not always correspond to improvements in O 2 delivery, shown by prolonged recovery (147). Insufficient O 2 delivery, prior to revascularization, may have altered the biochemical process of the metabolic pathway, which suggests that, in spite of immediate improvement in symptoms and hemodynamic parameters following revascularization, return to normal biochemical function may occur over a prolonged period of time.…”
Section: Mitochondrial Disease Mitochondrial Disease (Md)mentioning
confidence: 98%
See 1 more Smart Citation
“…While some studies reported hopeful outcomes of revascularization, linking to better bioenergetic status and muscle performance, other studies reported poor correlation of the improvement in hemodynamics measured by the ankle pressure index (API) and 31 P NMR index. While immediate improvements in hemodynamic responses and exercise tolerance may be seen after revascularization, the NMR index may not always correspond to improvements in O 2 delivery, shown by prolonged recovery (147). Insufficient O 2 delivery, prior to revascularization, may have altered the biochemical process of the metabolic pathway, which suggests that, in spite of immediate improvement in symptoms and hemodynamic parameters following revascularization, return to normal biochemical function may occur over a prolonged period of time.…”
Section: Mitochondrial Disease Mitochondrial Disease (Md)mentioning
confidence: 98%
“…Accordingly, PCr resynthesis rate responses during recovery from exercise in vascular disease population show a very slow recovery pattern, similar to those seen in mitochondrial disease population. A study by Zatina et al (147) examined calf muscles of 214 limbs with peripheral vascular disease. Resting 31 P NMR spectra showed the impairment of oxidative metabolism only in limbs with severe ischemia.…”
Section: P Mrs In Muscle Studiesmentioning
confidence: 99%
“…4 However, reestablishing large arterial blood supply to ischemic tissues may not completely correct the underlying microvascular and/or metabolic dysfunction in muscle tissues. 5,6 An approach to assess tissue hemodynamics and metabolism in the ischemic muscle of a lower extremity could enable evaluation of revascularization success and potentially elucidate the pathophysiology contributing to the incomplete functional benefit.…”
Section: Introduction 1peripheral Arterial Disease and Revascularizamentioning
confidence: 99%
“…to an overall decrease in biomechanical efficiency. On the other hand, a metabolic disturbance that lowers the efficiency of ATP resynthesis by oxidative phosphorylation [3][4][5][6][7][8][9][10][11][12] cannot be ruled out.…”
Section: Introductionmentioning
confidence: 96%